2015
DOI: 10.1038/nature14280
|View full text |Cite
|
Sign up to set email alerts
|

hiCLIP reveals the in vivo atlas of mRNA secondary structures recognized by Staufen 1

Abstract: AbstractmRNA structure is important for post-transcriptional regulation, largely because it affects binding of trans-acting factors 1 . However, little is known about the in vivo structure of full-length mRNAs. Here we present hiCLIP, a high-throughput technique to identify RNA secondary structures interacting with RNA-binding proteins (RBPs) in vivo. Using this technique to investigate RNA structures bound by Staufen 1 (STAU1), we uncover a dominance of intra-molecular RNA duplexes, a depletion of duplexes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
304
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(312 citation statements)
references
References 66 publications
(80 reference statements)
8
304
0
Order By: Relevance
“…Protein recruitment by lncRNAs www.rnajournal.org 2011 modifications throughout the transcriptome (Hodgkinson et al 2014;Rabani et al 2014;Alarcon et al 2015;Sugimoto et al 2015) could serve as additional determinants to guide PRC2 recruitment, although evidence for this is lacking in the case of PRC2.…”
Section: Promiscuous Rna Binding By Prc2mentioning
confidence: 99%
“…Protein recruitment by lncRNAs www.rnajournal.org 2011 modifications throughout the transcriptome (Hodgkinson et al 2014;Rabani et al 2014;Alarcon et al 2015;Sugimoto et al 2015) could serve as additional determinants to guide PRC2 recruitment, although evidence for this is lacking in the case of PRC2.…”
Section: Promiscuous Rna Binding By Prc2mentioning
confidence: 99%
“…The SBS is formed by intra-molecular base-pairing within the 3 ′ UTR, by inter-molecular base-pairing between two different 3 ′ UTRs (Gong et al 2013) or between an mRNA 3 ′ UTR and a long noncoding RNA (lncRNA) (Gong and Maquat 2011). In contrast, another study reported that STAU1 binds preferentially to intra-molecular duplexes in 3 ′ UTRs, but hardly binds to inter-molecular RNA structures (Sugimoto et al 2015).…”
mentioning
confidence: 99%
“…Thus, in the presence of WT1, there is an increase in the number of stable intramolecular RNA interactions, supporting a role for WT1 as a nucleating center for these interactions. Recent studies with the dsRNA-binding protein Staufen (Sugimoto et al 2015) show secondary RNA structures to be common and functionally important for gene expression. WT1 interaction at the 3 ′ UTR of targets also shows secondary structures, suggesting a role in regulating RNA stability.…”
Section: Utr Of Mrnasmentioning
confidence: 99%